(untitled) (Journal of Dhaka Medical College, 2011)
Objective: To evaluate the diagnostic efficacy of computed tomography (CT) guided transthoracic fine needle aspiration cytology (FNAC) in the diagnosis of intrathoracic masses not approachable by ultrasound. Materials and Methods: CT guided FNAC of intrathoracic masses was done in 100 patients and they were followed up to the final diagnosis. The diagnostic accuracy, sensitivity, specificity, positive and negative predictive values of the procedures were calculated. Results: The sensitivity, specificity, accuracy, positive predictive value and negative predictive value of CT guided transthoracic FNAC were 93.85%, 100%, 96%, 100% & 89.74% respectively for the diagnosis of sonographically nonapproachable malignant intrathoracic masses and 94.29%, 98.46%, 97%%, 97.06% & 96.97% respectively for benign intrathoracic masses. Conclusion: CT guided transthoracic FNAC is a highly sensitive and specific procedure in the diagnosis of intrathoracic masses that are not approachable by ultrasound. Keywords: Computed tomography; Fine needle aspiration cytology; Intrathoracic masses. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8568 J Dhaka Med Coll. 2011; 20(1) :25-31